THE CONCEPT OF INTERNAL CONTROL SYSTEM: THEORETICAL ASPECT - Lakis, Vaclovas; Giriūnas, Lukas (Ekonomika, 2012)
Analysis of the concept of internal control system is an important subject that involves the analysis of the latest scientific results, and on its basis to perform an updated analysis of the concept of internal control system which meets the modern business conditions and tendencies. Such an assumption has been made upon exploring famous scientists’ concepts of internal control system, in which the basic values needed for internal control system: (honesty, trust, respect, openness, skills, courage, economy, initiative, etc.) were not included. Only a modern concept of internal control might ensure an effective internal control system.The main purpose of the authors was to explore control, the concepts and conceptions of control, internal control and the system of internal control, as well as to present their own idea of the concept of internal control system and to compile a structural scheme of their conception. The structural scheme may alleviate the process of compiling a new model of an effective internal control system. The structural scheme of the conception may also be used in compiling a model of internal control system in different branches of industry.